2021
DOI: 10.1016/j.ijid.2021.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Population seroprevalence of SARS-CoV-2 antibodies in Anambra State, South-East, Nigeria

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 16 publications
1
25
3
Order By: Relevance
“…In Nigeria, a small convenience sample of different venues in Niger State conducted in June 2020 found a seroprevalence of 25.4% [14]. Another study found 45.1% seroprevalence among a small sample of health workers in Ibadan, Nigeria [15], while seroprevalence of 17.4% (range 5.4% -31.9%) was reported in surveys conducted in December 2020 in the 21 Local Government Areas of Anambra State [16].…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, a small convenience sample of different venues in Niger State conducted in June 2020 found a seroprevalence of 25.4% [14]. Another study found 45.1% seroprevalence among a small sample of health workers in Ibadan, Nigeria [15], while seroprevalence of 17.4% (range 5.4% -31.9%) was reported in surveys conducted in December 2020 in the 21 Local Government Areas of Anambra State [16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent Zambian postmortem study suggested that many people who die have an undiagnosed SARS-CoV-2 infection 4. Various studies have determined the seroprevalence in Africa 5–13. A recent systematic review has estimated it to be approximately 22%, with highest seroprevalence in central Africa 5.…”
Section: Introductionmentioning
confidence: 99%
“…, 2020 ) to 4.2% ( Kammon et al. , 2020 ) in Libya, from 16.1% ( Okpala et al. , 2021 ) to 42.0% ( Ijeoma et al.…”
Section: Resultsmentioning
confidence: 99%